Modulating the Wnt/Β-Catenin Pathway to Enhance Wool Fiber Fineness in Sheep: Subject Review - ZinAlabidin, Mohammed M; Tawfeeq, Mustafa Muwafaq; Murshed, Wael Majeed (American Journal of Biology and Natural Sciences, 2025)
This review summarises the important role of the Wnt/β-catenin signal pathway in the development of wool fineness and quality traits in sheep. Here, we combined these results and performed multi-omics analysis with machine-learning algorithms, upon a systematic review of >120 peer-reviewed studies (2010–2024) and unpublished field surveys. There are reports on SNPs of CTNNB1 and LRP6, as well as CRISPR/Cas9-mediated knock-outs of FGF5, extending Anagen, increasing density of secondary follicles, reducing average fiber diameter by 1–2 µm and increase of yield can reach by 18 %. Supplementary feeding of organic zinc and selenium together with PPD II almost doubled nuclear β-catenin activity; however, chronic heat stress shortened Anagen and increased fiber thickness. Oral pulse dosing of GSK-3β inhibitor CHIR-990218 increased Comfort Factor by 6 points and decreased fiber diameter by approximately 1 µm without systemic toxicity, whereas recombinant DKK1 served as an effective counter-screen for dose optimization. Economic modelling suggests that a 1-micron reduction in fibre diameter increases the price for scoured wool by 8–10 %, thus enabling breeding and/or pharmacological intervention to be recouped over two shearings in a flock of 1 000 ewes. Current barriers include the risks of off-target editing, fragmented regulatory landscape, and consumer acceptance of transgenic animals. We propose therefore a stepping-stone to our survival: (i) combining selection for specific Wnt markers with micro-dosing of GSK-3β inhibitors and early-warning omics dashboards, currently sighted alongside a single ethical–regulatory guideline as a roadmap for economicisation and environmental stewardship of the Merino wool industry.